1981
DOI: 10.1177/004051758105100604
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Distribution of Perimeter, Cell-Wall Area and Thickness, and Shape in Raw and Slack-Mercerized . Single Cotton Fibers

Abstract: A study of the cross-sections of single cotton fibers revealed that perimeter, cell-wall thickness, and cell-wall area are normally distributed, and that the parameters of the normal, or Gaussian, distribution can be used to describe these physical .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…7 to 10 times) and smaller sample sizes (n ¼ 200). Chauhan et al 52 also measured the cross-sectional properties of various cotton genotypes using a similar method to Petkar et al 21 (and the same sample number) at 45, 55, and 65 DPA stages of development. The Chauhan et al 52 results were similar, except that increases in fiber perimeter with increasing developmental age were detected.…”
Section: Effects Of Genotype and Defoliation Timingmentioning
confidence: 99%
See 1 more Smart Citation
“…7 to 10 times) and smaller sample sizes (n ¼ 200). Chauhan et al 52 also measured the cross-sectional properties of various cotton genotypes using a similar method to Petkar et al 21 (and the same sample number) at 45, 55, and 65 DPA stages of development. The Chauhan et al 52 results were similar, except that increases in fiber perimeter with increasing developmental age were detected.…”
Section: Effects Of Genotype and Defoliation Timingmentioning
confidence: 99%
“…Chauhan et al 52 also measured the cross-sectional properties of various cotton genotypes using a similar method to Petkar et al 21 (and the same sample number) at 45, 55, and 65 DPA stages of development. The Chauhan et al 52 results were similar, except that increases in fiber perimeter with increasing developmental age were detected. Those authors suggested that changes in perimeter during fiber development were dependent on the opposing factors of increasing maturity and increasing "coarseness," and that a propensity for greater maturity tends to go with lower perimeter fibers.…”
Section: Effects Of Genotype and Defoliation Timingmentioning
confidence: 99%
“…The theoretical frequencies were worked out using Equation 1. The X2 values obtained give the goodness-of-fit of normal distribution as shown in columns 10 to 13, where nearly half the total X2 values are nonsignificant, indicating that the frequency distribution of the secondary wall thickness values may be normal.…”
Section: Secondary Wall Thicknessmentioning
confidence: 99%
“…Schloemer [3] was the first to consider shape factor in terms of area and perimeter, since obviously any variation in shape factor is mainly due to a variation in these. Chauhan et al ( 1 ] studied the variation in fiber characteristics such as perimeter, cell-wall area and thickness, and shape of raw and mercerized cotton fibers. In order to investigate changes in these parameters as a function of growth, these authors presented data on perimeter, cell-wall thickness, and cell-wall area of one cotton, Kalyan, and they observed that these fiber characteristics followed normal distribution for all three different growth periods.…”
mentioning
confidence: 99%